2014
DOI: 10.2495/uw140271
|View full text |Cite
|
Sign up to set email alerts
|

The development of integrated real time control to optimise storm water management for the combined sewer system of Rome

Abstract: Increasing urbanisation and intensification of human activities are common trends all over the world. The higher portion of impermeable urban surfaces often leads to well known effects on storm water runoff and its polluting potential for receiving waters. Despite the variety of structural solutions and management practices proposed to mitigate the operational and environmental impact of urban runoff, their application on existing drainage systems can often be either ineffective at a metropolitan scale or unfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For a watershed with limited flood risk, suppose it has a suitable layout of UDS networks and a large surplus capacity of UDS, the application of the MPC system for real-time control of UDS in urban flood risk mitigation should be more effective. For instance, Celestini et al [42] demonstrated that flood inundation could be fully mitigated by simple control rules. Also, AbouRjeily et al [28] suggested that flood inundation driven by a rainfall event with a return period of 5 years could be alleviated effectively by the real-time UDS control of the MPC system.…”
Section: Discussionmentioning
confidence: 99%
“…For a watershed with limited flood risk, suppose it has a suitable layout of UDS networks and a large surplus capacity of UDS, the application of the MPC system for real-time control of UDS in urban flood risk mitigation should be more effective. For instance, Celestini et al [42] demonstrated that flood inundation could be fully mitigated by simple control rules. Also, AbouRjeily et al [28] suggested that flood inundation driven by a rainfall event with a return period of 5 years could be alleviated effectively by the real-time UDS control of the MPC system.…”
Section: Discussionmentioning
confidence: 99%